A content analysis of Journal of Library Science in China in 2007–2016. Issue 4 (2nd October 2018) - Xie, Jingzhen; Sun, Lili
Abstract: A content analysis of JLSC's publications in 2007–2016 was conducted to investigate its publication patterns and research topics. Elements such as article titles, keywords, authors' affiliations, titles, disciplines, author collaboration and grant-funded projects were coded and examined. Findings indicate that libraries, information services, cataloging and classification, knowledge management and information retrieval were the most frequently discussed topics. Over 50% of the authors were LIS faculty members with librarian practitioners and LIS graduate students each representing about one-quarter of the total authorship. The percentage of case studies was not significant. Over half of the articles resulted from grant-funded projects. Collaborative writing was active.